The institutional perspective on outward foreign direct investment from China: the relationship between the government and firms - Cheng, Qian (2012)
China's outward foreign direct investment (OFDI) has increased considerably in the last few decades. The development of China's OFDI has distinct features, in particular the fact that the major investors undertaking large-scale deals are state-owned enterprises. However, they have few competitive advantages compared with their international counterparts. As mainstream theories have difficulty in providing a reasonable explanation of China's OFDI, this thesis analyses the Chinese government's home country measures (HCMs) and their effects on OFDI, contributing to the understanding of the institutional analysis in international business.